Successful pregnancy outcome in a case of Eisenmenger syndrome - Roy, Tuhin S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Eisenmenger syndrome is a very rare heart disease in pregnant women. Eisenmenger syndrome is defined as pulmonary hypertension resulting from an uncorrected left to right shunt of a VSD, ASD or patent ductus arteriosus (PDA), with subsequent shunt reversal and cyanosis. Pulmonary hypertension is the prognosis index. The high mortality risk (25-30%) is associated with pregnancy and the peripartum period due to cardiovascular collapse. Pregnancy should be discouraged and reliable contraception, preferably permanent sterilization, advised because of the extreme risk associated with pregnancy. Depo-Provera or progesterone implants are nonsurgical alternatives. Even first-trimester termination is associated with a maternal mortality rate of 5-10%. However, despite all the risks, a few patients deliver successfully with a good maternal and neonatal outcome. We presented a 27-year-old booked G1P0+0 admitted at 34 weeks gestation with Eisenmenger syndrome. She was treated medically during pregnancy, underwent elective caesarean section at 34 weeks of gestation delivered a baby and was subsequently discharged on the 15th postoperative day without any serious complications.